RCM Engineering & Services Sdn Bhd / Muhammad Amin M.H. Asri - M.H. Asri, Muhammad Amin (2017)
All praises be to Allah, Lord of the Universe, the Merciful and Beneficent to Prophet Muhammad S.A.W, His Companion and the people who follow His path. First and foremost, I would like to take this opportunity to express my sincerely gratitude and appreciation to my parents and my family for the support through my university years. Special thanks are due to RCM Engineering & Services Sdn. Bhd. for giving me a chance to undergo my industrial training. Thanks to my supervisor, Siti Ummirah binti Dosah and technicians for their guidance in order to successful in my industrial training. My further gratitude is to all the engineers, team leaders and technicians who have assisted me in completing this internship, especially in completing my project. To the Student Industrial Internship Unit of International Islamic University Malaysia, I would also like to take this chance to thank them for organizing this course and help me in finding the host company, as it enables me to widen my perspective on the real engineering and working world. Last but not least, not to forget family and friends who gave me the supports towards the completion this course and project. Thank you very much for the wonderful hands.